Plasma assisted deposition of TaB₂ coatings by magnetron sputtering system - Yakovin, S.; Zykov, A.; Dudin, S.; Farenik, V.; Goncharov, A.; Shelest, I.; Kuznetsov, V. (Вопросы атомной науки и техники, 2017)
In the present paper the results of TaB₂ coating deposition in cluster set-up comprising a low pressure planar magnetron and an inductive plasma source are presented. The system allows to control independently the fluxes of the deposited Ta and B atoms from the sputtered TaB₂ target, and the fluxes of argon ions and electrons from the inductive plasma. Low argon pressure in the chamber allows the deposition process in the collisionless regime, providing the composition of the deposited film which is very close to the stoichiometry of the sputtered target. The correlation of the TaB₂ coating structure with the substrate voltage in the range from -50 to +50 V is demonstrated. Представлены результаты нанесения покрытий TaB₂ в кластерной установке, включающей плоский магнетрон низкого давления и индукционный источник плазмы. Система позволяет контролировать независимо друг от друга как потоки осаждаемых атомов Та и В из распыляемой мишени TaB₂, так и потоки ионов аргона и электронов из индукционной плазмы. Низкое давление аргона в камере позволяет проводить процесс напыления в бесстолкновительном режиме, обеспечивая состав осаждённой плёнки, очень близкий к стехиометрическому составу распыляемой мишени. Показана взаимосвязь структуры покрытия TaB₂ с напряжением смещения на подложке (в диапазоне от -50 до +50 В) и с плотностью ионного тока. Представлено результати нанесення покриттів TaB₂ у кластерній установці з плоским магнетроном низького тиску та індукційним джерелом плазми. Система дозволяє контролювати незалежно один від одного як потоки осаджуваних атомів Та й В з мішені TaB₂, так і потоки іонів аргону і електронів з індукційної плазми. Низький тиск аргону в камері дозволяє проводити процес нанесення в режимі без зіткнень, забезпечуючи склад синтезованою плівки, дуже близький до стехіометричного складу мішені. Показано взаємозв'язок структури покриття TaB₂ з напругою зсуву на підкладці (в діапазоні від -50 до +50 В) і з щільністю іонного струму.